If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3d = (-23) 4 + 3d = -23 Solving 4 + 3d = -23 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3d = -23 + -4 Combine like terms: 4 + -4 = 0 0 + 3d = -23 + -4 3d = -23 + -4 Combine like terms: -23 + -4 = -27 3d = -27 Divide each side by '3'. d = -9 Simplifying d = -9
| 3p+7=s | | 4y^2-16+12=0 | | 2(8v+8)=9(2v+3) | | -53=3+7x | | 3x-9=17-3x | | 4+3d=23 | | 2(8)-2x=10 | | 3t+10=58 | | 2x-41=x | | 3r+24=63 | | 9[e+3]=11e-13 | | 90=2x+3x-5 | | 47x+1=65x | | 2x-4(x+2)=-8+5x-33 | | 5+6*8+h=7*3+h | | 23-3m=5m+7 | | (2y^2+x)(y^2-7x)= | | (-1+6i)(3-5i)= | | 8[d+5]=12d-8 | | 3x-9=3(5-3x) | | 70-40+10x=12x+40-40 | | 3(x-3)-2(x+1)= | | 96t-16t^2-80=0 | | 5x+5=-115 | | 4+5x+9=7x-1 | | 4x^2-7x+11=9x+4 | | 0.75m+3=9 | | 2x-4(3-x)=7x+5 | | 5a-(2-a)=2a-14 | | 32t+-12=3t+42 | | 4[a+3]=2a+62 | | 24513465134+134613461= |